Predictors of malaria among pregnant women attending ante-natal clinic in general hospital in Zamfara State, Nigeria - Hadiza, Kallamu (2015)
Malaria is a major health problem with global concern. It is one of the world’s most prevalent serious infectious diseases, with approximately 250 million cases and one million deaths per year. Nigeria is included among the 45 countries that are endemic for malaria, and about 97% of the population were at risk especially children and pregnant women. Objectives: To determine the predictors of malaria among pregnant women attending ante-natal clinic in general hospitals Zamfara State, Nigeria. Methodology: A case control study was conducted among pregnant women attending ante-natal clinic in general hospital Zamfara State, Nigeria. A total of 522 pregnant women 261 cases and 261 controls were selected using multistage random sampling. Cases and controls in this study were defined as a pregnant woman attending antenatal clinic from the selected general hospitals in Zamfara, confirmed with and without malaria respectively, using giemsa staining method based on their medical records. Face to face interview and self-administered pretested questionnaire in English and Hausa languages was used to obtain information based on their socio demographic characteristics, maternal history, knowledge, attitude and preventive practices regarding malaria from May to August 2014. The data was analysed using SPSS version 21, chi square test was used to determine the association between the group’s case and controls, and logistic regression was used to determine the predictors of malaria. Significant level (p) was set at 0.05. Results: The overall response rate was 89.8%. Chi square results shows that pregnant women ≤ 25 years of age were more significantly associated with malaria than those with older age ( = 17.835, df = 3, p < 0.001), informal education ( = 166.619, df = 4, p < 0.001), unemployment ( = 220.519, df = 2, p < 0.001), monthly income < 5000 naira ( = 353.841, df = 2, p < 0.001), first trimester ( = 27.754, df = 2, p < 0.001). Other essential significant variables include low level of knowledge on malaria ( = 96.632, df = 1, p < 0.001), negative attitude ( = 248.309, df = 1, p < 0.001) and low level of preventive practices ( = 148.761, df = 1, p < 0.001) are significantly associated with malaria. Predictors of malaria include informal education (AOR = 8.340, 95% CI = 3.170, 21.947), unemployment (AOR = 8.437,95% CI = 1.695, 42.007), monthly income < 1000 naira (AOR = 18.809, 95% CI = 3.829, 92.393), low knowledge (AOR = 5.363, 95% CI = 2.130, 13.501), negative attitude (AOR = 33.831, 95% CI = 12.749, 89.778) and no practice (AOR = 44.622,95% CI = 3.829, 92.392). Conclusion: This study has identified informal education, unemployment, low monthly income, low level of knowledge, negative attitude and poor preventive practices as predictors of malaria among pregnant women attending ante-natal clinic in general hospitals in Zamfara State, Nigeria. The findings in this study can be used by policy makers to plan how to tackle the risk factors of malaria among pregnant women in the State.